Adaptive natural killer cell response to cytomegalovirus and disability progression in multiple sclerosis. (May 2016) - Martínez-Rodríguez, Jose E; Cobo-Calvo, Alvaro; Villar, Luisa M; Munteis, Elvira; Blanco, Yolanda; Rasal, Raquel; Vera, Andrea; Muntasell, Aura; Alvarez-Lafuente, Roberto; Saiz, Albert; Alvarez-Cermeño, Jose C; Martínez-Yélamos, Sergio; et al.
Background: Human cytomegalovirus (HCMV) causes a highly prevalent infection which may have a multifaceted impact on chronic inflammatory disorders. However, its potential influence in multiple sclerosis (MS) remains controversial. The HCMV-host interaction may induce an adaptive reconfiguration of the natural killer (NK) cell compartment, whose hallmark is a persistent expansion of peripheral NKG2C+ NK-cells. Objective: The purpose of this study was to evaluate whether the HCMV-driven NKG2C+ NK-cell expansion is related to the MS clinical course. Methods: Multicentre analysis of NKG2C expression and genotype according to HCMV serostatus and time of assignment of irreversible disability scores in 246 MS patients prospectively followed up in our institutions. Results: NKG2C expression was unrelated to disease-modifying drugs, remained stable under steady-state conditions, and was higher in HCMV(+) NKG2C +/+ homozygous individuals. NKG2C+ NK-cell expansion in HCMV(+) patients, as compared to HCMV(+) or HCMV(–) patients with lower NKG2C+ NK-cells proportions, conferred a lower risk of progression in Cox regression analysis (Expanded Disability Status Scale (EDSS)>3.0, hazard ratio (HR)=0.33, 95% confidence interval (CI) 0.15–0.71, p =0.005; EDSS>5.5, HR=0.23, 95% CI 0.07-0.74, p =0.014). Neither HCMV serostatus nor NKG2C genotype appeared to be related to disability progression. Conclusions: HCMV may exert a beneficial influence on MS, decreasing the risk of disability progression in those patients displaying a virus-driven NKG2C+ NK-cell expansion.